"The History of Us": Social Science, History, and the Relations of Family in Canada - Comacchio, Cynthia (Labour/Le Travailleur, 2000)
Abstract This essay provides a selective overview of the Canadian historiography on family. The roots of family history not only extend backwards much further than the "new social history" bom of the tumultuous 1960s, they are buried deep in several other disciplines, most notably sociology, anthropology, and demography, whose practitioners were concerned as much with the historical process of family change as with the state of families contemporary to their times. I consider how pioneering social scientists, by grappling with the family's relationship to structural change, historicized early 20th century family studies and offered up many of the questions, concepts, theories, and methods that continue to inform historical scholarship on families. Turning to the body of historical publications that followed in the wake of, and were often inspired by, the "new social history," I highlight the monograph studies that served as signposts in the field's development, especially for what they have revealed about the critical nexus of family, work, and class. The historiography mirrors the family's history: "family" consists of so many intricately plaited strands that separating them out is frustrating and often futile. I have attempted to classify this material both topically and chronologically within broad categories, but the boundaries blur so that most of these works could fit as comfortably in several others. Many of them, in fact, will be recognized as important contributions to fields such as labour, ethnic, women's, or gender history rather than as works of family history per se.